2014
DOI: 10.1093/infdis/jiu526
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Coxiella burnetii by Toll-like Receptors and Nucleotide-Binding Oligomerization Domain-like Receptors

Abstract: The TLR1/TLR2 heterodimer and NOD2 are important recognition receptors for the induction of cytokine responses against C. burnetii in humans. Furthermore, an interesting finding was the divergent recognition of C. burnetii Nine Mile and C. burnetii 3262.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…C57BL/6 (B6) bone marrow-derived macrophages (BMDMs) do not permit the robust intracellular replication of C. burnetii NMII (56). Restriction of NMII replication is mediated in part by TLR2 signaling (58), and TLR2 is required for the production of proinflammatory cytokines by human PBMCs in response to C. burnetii phase I infection and mouse macrophages in response to both C. burnetii phase I and phase II (58,61). However, the roles of other TLRs or the signaling adaptor MyD88 or Trif in enabling B6 macrophages to restrict NMII replication or mount an effective cytokine response are largely unknown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…C57BL/6 (B6) bone marrow-derived macrophages (BMDMs) do not permit the robust intracellular replication of C. burnetii NMII (56). Restriction of NMII replication is mediated in part by TLR2 signaling (58), and TLR2 is required for the production of proinflammatory cytokines by human PBMCs in response to C. burnetii phase I infection and mouse macrophages in response to both C. burnetii phase I and phase II (58,61). However, the roles of other TLRs or the signaling adaptor MyD88 or Trif in enabling B6 macrophages to restrict NMII replication or mount an effective cytokine response are largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…C. burnetii lipid A is thought to be poorly stimulatory for TLR4 and is capable of behaving as a TLR4 antagonist in human PBMCs (58). Abolishing TLR4 alone does not impact cytokine responses to phase I or II infection in vitro, and the absence of TLR4 does not affect NMII replication within mouse macrophages (58,61). Given that TLR2 responds so robustly to NMII, we wondered whether a role for TLR4 could be revealed in the absence of TLR2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed similar results with in vitro infection of peritoneal and pulmonary macrophages (data not shown). Also, recently it has been shown that TLR1/ TLR2 in human cells can be an important recognition receptor for C. burnetii infection, leading to robust cytokine responses (36). Therefore, the absence of TLR2 signaling may allow for the development of permissive populations of macrophages for C. burnetii growth.…”
Section: Discussionmentioning
confidence: 99%